Finite element modeling for prediction the effect of nose radius on cutting forces for titanium (Ti-6Al-4V) alloy - Ali M.H.; Mohamed B.; Ansari M.N.M.; Khidhir B.A. (International Hellenic University - School of Science, 2023)
This paper presents a study the effect of nose radius (Rz-mm) on the cutting forces during the machining process in a face milling operation for titanium (Ti-6Al-4V) alloy. To improve the prediction of the effect of nose radius (Rz-mm) on cutting force components so the cutting tests were performed with various nose radiuses (Rz-mm) while the depth of cut (d-mm), feed rate (f-mm/tooth) and cutting speed (vc-m/ min) were remained constant. The main cutting force (Fc) and feed cutting force (Ft) were measured by using the ABAQUS/EXPLICIT software simulation through the development a two-dimensional orthogonal cutting process of finite-element modeling. The results led to the conclusion that the nose radius (Rz-mm) has affected directly on the cutting force components. An increase in the nose radius (Rz-mm) led to more convergence in terms of behavior between the main cutting force (Fc) and feed cutting force (Ft) and its direct effect on the quality and quantity of product. 2012 Kavala Institute of Technology.